Responsive neurostimulation for patients with refractory mesial temporal lobe epilepsy: A systematic review and meta-analysis - Eshita Sharma; Beatriz Westphalen Pomianoski; Rabbia Jabbar; Ayesha Ayesha; Yasmin Picanco Silva; Paweł Łajczak; Aisha Rizwan Ahmed; Oguz Kagan Sahin; Mir Wajid Majeed; Mohammed Raake; Walter Fagundes; Giovani Noll (Epilepsy & Behavior Reports)
Responsive neurostimulation (RNS) is a well-established adjuvant therapy for reducing seizure frequency in adults with medically refractory partial-onset seizures, particularly in individuals who are either not candidates for surgical resection or remain seizure-prone post-surgery. However, its effectiveness in patients with mesial temporal lobe epilepsy (MTLE) remains unclear. This meta-analysis evaluates the efficacy of RNS therapy in individuals with medically refractory MTLE. A systematic search of PubMed, Cochrane, and Scopus databases was conducted to identify eligible studies. Outcomes assessed included mean seizure frequency reduction, responder rate (proportion of patients achieving ≥50 % reduction in seizure frequency), and the proportion of patients achieving seizure freedom within six months of follow-up. Statistical analyses were performed using STATA. Seven observational studies involving 207 patients were included. RNS was associated with a mean seizure frequency reduction of 68.76 % (95 % CI 57.16–80.37 %; I2 = 81.68 %), a responder rate of 67.58 % (95 % CI 46.51–88.66 %; I2 = 94 %), and seizure freedom within six months in 28.94 % of patients (95 % CI 3.03–54.86 %; I2 = 88 %). Moderate to high heterogeneity was observed across the studies. RNS may represent a viable therapeutic option for patients with MTLE, demonstrating substantial reductions in seizure frequency and a notable proportion of patients achieving seizure freedom. Additional studies are needed to confirm these findings and to explore the comparative efficacy and safety of RNS therapy in relation to other treatment options.